Effect of biochar and Tithonia compost on physical properties of post-coal mining soil - Wiskandar, Wiskandar; Ajidirman, Ajidirman (Journal of Degraded and Mining Lands Management, 2024)
Biochar and Tithonia compost are alternative materials used to ameliorate soil properties. The application of these two types of ameliorants in ex-coal mining areas aims to improve the physical properties of the soil and its effect on soybean growth and yield. The research was designed in the form of a polybag experiment conducted in a greenhouse. The soil used for this research was taken from the surface layer of ex-coal mining pits. The treatment levels tested consisted of three biochars and four Tithonia composts. Each treatment level was 0, 5, and 10 t biochar ha-1 and 0, 5, 10, and 15 t Tithonia compost ha-1. The research units were arranged in a completely randomized design. The results showed that applying 10 t biochar ha-1 and 15 t Tithonia compost ha-1 decreased soil bulk density, increased total pore space, aggregate stability, and soil water content capacity, and improved soybean growth and yield. The soil physical properties and soybean improvement were not significantly different from those due to the application of 5 t Tithonia compost ha-1.